Visual Depictions of Religion in Children’s Picture Books - Wicks, Don A.; Freeburg, Darin; Goldsmith, Douglas (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
How children are introduced to concepts of faith is a sensitive matter. One approach used by both religious and secular organizations is children’s literature, including children’s picture books. This paper offers an exploratory study of how religion and spirituality are depicted in such literature. La manière d’introduire les enfants au concept de la foi est un sujet délicat. Une approche utilisée par les organisations religieuses et non confessionnelles est la littérature jeunesse, y compris les livres d’images. Cette communication présente une étude exploratoire sur le traitement de la religion et de la spiritualité dans la littérature jeunesse.